Finland : Report on the Observance of Standards and Codes- FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2008)
This report reviews observance of Standards and Codes for the Financial Action Task Force (FATF) 40+9 Recommendations and the Anti-money Laundering and Combating the Financing of Terrorism (AML/CFT) measures in place in Finland. The report describes the level of compliance with the FATF 40+9 Recommendations, and contains recommendations on how the AML/CFT system could be strengthened. The report reveals that Finland has a good legal structure to combat money laundering and terrorist financing.